Packaging And Promotion Effect On Purchase Decision (Survey of Maykroni consumers in Tasikmalaya City) - Fahmi Nurul Awalin; Ari Arisman; Suci Putri Lestari (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the simultaneous and partial effect of the Effect of Packaging and Promotion on Buying Interest (Survey of Maykroni consumers in the City of Tasikmalaya. The research method used in this study is a quantitative research method with a survey approach. The sampling technique used is incidental sampling and the sample used is incidental sampling. 100 respondents were taken. The analysis tool used was multiple regression equation. The results showed that Packaging and Promotion had a significant effect on the Buying Interest of Maykroni consumers in the City of Tasikmalaya. The partial packaging had a significant effect on the Buying Interest of Maykroni consumers in the City of Tasikmalaya. Partial promotion significant effect on consumer buying interest Maykroni in Tasikmalaya City.